Produksi Paku Diameter 5 mm, Panjang 50 mm, Tahan Karat Kapasitas 10 kg/Jam - Muhammad Yazid Bustomy; Syamsul Hadi; Zanetta Al Azhar; Mohammad Sheva Firdaus; Yudhistira Satria Nugroho (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2026)
Problems faced in the need for nails in the furniture industry, and various civil engineering works, which are uniform and standard sizes. The production objective is to obtain nails with a diameter of 5 x 50 mm, which are not easily rusted, with uniform and standard sizes. Production methods include: nail design with dimensions of 5 x 50 mm diameter; preparation of low carbon steel wire, AISI 1020, diameter 5 mm in the form of a coil with a diameter of 600 mm; straightening the steel wire coil through a die; cutting the tip of the pointed shape into a length of 50 mm; forming the nail head (haeding) with a head diameter of 8 mm and a head thickness of 1.5 mm; coating by dipping into molten zinc (hot dip galvanized) at a temperature of 500oC for 30 seconds; and quality control on shape, straightness, and dimensions. The production results are nails with a diameter of 5 x 50 mm which are rust-resistant, uniform and standard in size with a production cost of IDR 24,000/kg, a production process duration of 6 minutes/kg which has an impact on being used in construction, the furniture industry, and various civil engineering works wood, plastic, composites, thin metal plates, walls.